Nutritional knowledge, diet quality and nutritional status of school-going adolescents in rural and urban areas in West Aceh - Ranita Suri Dewi; Cesilia Meti Dwiriani; Ali Khomsan (AcTion: Aceh Nutrition Journal, 2024)
The primary nutritional problem of adolescents is the triple burden of malnutrition. Factors that trigger nutritional problems in adolescents include poor eating habits, low nutritional and socioeconomic knowledge, and sedentary activities. This study aimed to analyze differences in nutrition knowledge, diet quality, and their relationship with nutritional status among rural and urban school adolescents in West Aceh. This study used a cross-sectional design, involving 312 adolescent schools in West Aceh in 2023. Data on nutritional knowledge were collected using a questionnaire filled out by the subjects themselves, intake data using 2x24-hour food recall, and anthropometric measurements such as BAZ and Percent Body Fat (PBF) using BIA scales and microtoice. Data were analyzed using Mann-Whitney and Spearman rank tests. There were significant differences in family characteristics, nutritional knowledge, and diet quality between the rural and urban school adolescents (p<0,05). There was a significant positive relationship between nutritional knowledge and diet quality and BAZ and PBF (p<0,05) only among rural school adolescents. In conclusion, family characteristics, nutritional knowledge, and diet quality differed significantly among the adolescents by region. In rural areas, nutritional knowledge and diet quality were significantly associated with BAZ and PBF. School adolescents' knowledge and diet quality remain low; therefore, nutrition education related to balanced nutrition guidelines is required.